2018
DOI: 10.21079/11681/26625
|View full text |Cite
|
Sign up to set email alerts
|

Pollutant concentration in runoff at McMurdo Station, Antarctica

Abstract: The plan to modernize McMurdo Station involves constructing large buildings for more efficient facilities and infrastructure. Foundation design for these large buildings will require understanding of the mechanical properties of the native soil. This study is the first that we are aware of to conduct uniaxial compression tests on materials from McMurdo Station in their frozen state. The testing used in this study emulates specific ground conditions measured on-site. Reconstituted specimens of well-graded grave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Some of the natural runoff flow paths change over time due to erosion, which depends on the intensity of the snowmelt runoff. A study done by Affleck et al (2014) showed flow discharge during the austral summer ranges from 74 to 4239 m 3 /day, indicating runoff does occur at the Station. Consideration for the hydrological flow paths established at the site is important for understanding soil reuse standards and guidelines.…”
Section: Hydrologymentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the natural runoff flow paths change over time due to erosion, which depends on the intensity of the snowmelt runoff. A study done by Affleck et al (2014) showed flow discharge during the austral summer ranges from 74 to 4239 m 3 /day, indicating runoff does occur at the Station. Consideration for the hydrological flow paths established at the site is important for understanding soil reuse standards and guidelines.…”
Section: Hydrologymentioning
confidence: 99%
“…Because of the slow biological degradation of the legacy pollutants within polar environments, the contaminants persist, frozen in place, and accumulate, lasting indefinitely. Contaminants related to the above disturbances (hydrocarbons and metals) were specifically found to be elevated in runoff during the snowmelt period (Affleck et al 2014). Kennicutt et al (2010) and Klein et al (2008Klein et al ( , 2012 collected and analyzed several hundred soil samples over nine years to monitor the extent of the environmental impact of the various contaminants.…”
Section: Figures and Tablesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, moraines, permafrost polygons, massive ice wedges, and other shallow geomorphology features are still visible at the station borders, suggesting their prior existence also on station grounds. Secondary impacts from McMurdo activities include increased airborne dust from vehicle traffic, which has altered snowpack albedo; associated melt water runoff from local snowfields; a deepening of the active layer or complete thawing of permafrost; and increased stream flow and erosion (Campbell et al, 1994;Klein et al, 2008aKlein et al, , 2008bAffleck et al, 2012Affleck et al, , 2014aAffleck et al, , 2014band Affleck and Carr, 2015). Accidental or historical human activity, such as chemical spills, fuel leaks, garbage and construction debris burial, is also prevalent at McMurdo Station, resulting in increased subsurface complexity relative to other similar near-surface geology study sites.…”
Section: Introductionmentioning
confidence: 99%